47 Prognostic markers in stage 1 oral cavity squamous cell carcinoma. Issue 5 (May 2015) - ,; Vaittinen, S.; Grénman, R.; Kinnunen, I.; Irjala, H.
Abstract : Over 260, 000 people are diagnosed with oral cavity squamous cell carcinoma (OCSCC) each year. While human papilloma virus infection has been linked to oropharyngeal SCC and a favorable clinical outcome, this link in OCSCC is more controversial. Several biomarkers in SCC of the head and neck have been investigated but adaptation to clinical decision making remains limited. We have studied a panel of established biomarkers by immunohistochemical analyses in order to aid patient staging in early stage OCSCC. Our pilot study indicated that the combination of HIF1 α (a cancer-associated hypoxia marker) and CD44 (a cell adhesion molecule) enabled us to distinguish patient populations whose clinical outcomes differed dramatically. All patients with tumors containing the HIF1 α (low) CD44(hi) signature remained in therapy-free remission over the five-year follow-up, whereas patients with HIF1 α (hi) CD44(low) tumors had a 75% recurrence rate in our sample size of 35 patients. These results are further being tested on a larger sample size with 133 patients.